(untitled) (Iraqi Journal of Civil Engineering, 2017)
In the civil engineering, the prediction of cracks for tunnel lining is too hard because it depends by different factors for example concrete strength, tunnel operation conditions, stress and geological surroundings. The aim of this study is to design a Fuzzy inspect System (FIS) for evaluating the concrete cracks of tunnel lining. Fuzzy logic is a method to signify a type of uncertainty which is understandable for user. The system has been designed to meet permit crack formula that issued in “Highway Tunnel Design Specifications”. When the maximal permit crack width as example is chosen as 0.7mm, 1.2mm and 3.3mm separately the fuzziness set accordingly is Minor , moderate and severe. The average error for the predicted crack (element sample) in FIS is 8.34%. The fuzzy evaluation model is based on the information of a real in-service PESHRAW highway tunnel, which reflects field status. Therefore, this evaluation is comfortable.